Environmental impact assessments and mitigation - Manyuchi, Musaida Mercy; Mbohwa, Charles; Muzenda, Edison; Sukdeo, Nita (Boca Raton, FL CRC Press, an imprint of Taylor & Francis Group, LLC, 2021)
"Environmental Impact Assessments and Mitigation examines various assessments for developmental projects in the housing, mining, energy, and waste management areas. As the world continues to shift toward concerns over climate change and environmental protection issues, developmental projects must have environmental impact assessments (EIA) conducted as well as environmental management plans (EMP). This book describes how all phases of a project, from planning, to operation, to post operation, must consider potential environmental impacts and their mitigation. Features : Presents numerous sustainable development considerations for key industries, discusses how environmental impact assessments are prepared for each stage of a project, describes different environmental management plans for established projects, offers mitigation plans for various potential environmental impacts , includes practical examples from the construction, manufacturing, transport, and mining industries. Useful for practicing professional engineers as well as upper-level students, this book covers all aspects of environmental impact assessments from start to finish."--Provided by publisher.
Includes bibliographical references and index.
Keywords: Environmental impact analysis